Analysis of gender and leadership role competencies, perceptions and stereotypes in an organisational context - O. M. Samuel; I. Mokoaleli (South African Journal of Business Management, 2017)
Powell (1990) contended that the differences between women and men leadership style is mostly based on perception and stereotype and concluded that there are "no differences" between men and women managers. This article evaluated causal linkages between employees' perception of both managerial and functional competencies and stereotype of male and female managers using a conglomerate in South Africa. The study adopted survey strategy using quantitative research design. Respondents comprised of 383 conveniently sampled lower and middle level managers using the non-probability sampling technique. Using structural equation modelling (SEM) (AMOS) and inferential statistics, our analysis showed a positive association to establish that male managers are more competent than female managers (t = 21.01, p 01), while the SEM path between perceptions and managerial competence was found to be significant (t = 001 .05). We found a non-significant path between perceptions and functional competence (t = .10, p .05). Similarly, the path between perceptions and stereotyping was found to be non-significant (t = .07 .05). This findings further extend contemporary literature on gender and leadership roles and perhaps provided some insights regarding the continued underrepresentation of women in executive and top management positions in various organisations.
Keywords: 650